In silico Screening and Behavioral Validation of a Novel Peptide, LCGA-17, With Anxiolytic-Like Properties - Malyshev, Anton V.; Sukhanova, Iuliia A.; Zlobin, Alexander S.; Gedzun, Vasilina R.; Pavshintsev, Vsevolod V.; Vasileva, Ekaterina V.; Zalevsky, Arthur O.; Doronin, Igor I.; Mitkin, Nikita A.; Golovin, Andrey V.; Lovat, Maxim L.; Kovalev, Georgy I.; et al. (Frontiers in Neuroscience, 2021)
The aim of the study was to develop better anxiolytics and antidepressants. We focused on GABAA receptors and the α2δ auxiliary subunit of V-gated Ca2+ channels as putative targets because they are established as mediators of efficacious anxiolytics, antidepressants, and anticonvulsants. We further focused on short peptides as candidate ligands because of their high safety and tolerability profiles. We employed a structural bioinformatics approach to develop novel tetrapeptides with predicted affinity to GABAA receptors and α2δ. In silico docking studies of one of these peptides, LCGA-17, showed a high binding score for both GABAA receptors and α2δ, combined with anxiolytic-like properties in a Danio rerio behavioral screen. LCGA-17 showed anxiolytic-like effects in the Novel Tank Test, the Light-Dark Box, and the Social Preference Test, with efficacy comparable to fluvoxamine and diazepam. In binding assays using rat brain membranes, [3H]-LCGA-17 was competed more effectively by gabapentinoid ligands of α2δ than ligands of GABAA receptors, suggesting that α2δ represents a likely target for LCGA-17. [3H]-LCGA-17 binding to brain lysates was unaffected by competition with ligands for GABAB, glutamate, dopamine, serotonin, and other receptors, suggesting specific interaction with α2δ. Dose-finding studies in mice using acute administration of LCGA-17 (i.p.) demonstrated anxiolytic-like effects in the Open Field Test, Elevated Plus Maze, and Marble Burying Tests, as well as antidepressant-like properties in the Forced Swim Test. The anxiolytic effects were effectively blocked by bicuculline. Therefore, LCGA-17 is a novel candidate anxiolytic and antidepressant that may act through α2δ, with possible synergism by GABAA receptors.